KOROAPS - SYSTEM FOR A LARGE SCALE MONITORING AND VARIABLE STARS SEARCHING - Parimucha, S.; Baludansky, D.; Vadila, M. (Одеські астрономічні публікації, 2007)
We give an introduction information about the KOROAPS (KOsice ROztoky Automatic Photometry System). It is a system for a large scale automatic multicolor monitoring and variable stars searching. It is in a development at Safarik University in Kosice in cooperation with Roztoky Observatory . The system is now in a test operation at Roztoky Observatory . System consists of Nikkor photolense 2/200 equipped with SBIG ST8 CCD camera and set of the standard VRI photometric filters. It is placed on Celestron’s CG-5 Advanced mount. We give description of the basic properties of the instrument, data reduction pipeline and operational modes of the instrument.